Banku personāla tālākizglītības sistēma. - Vaivode, Daiga (Latvijas Universitāte, 2006)
Resumé The Paper researches the solutions for issues and problems in securing effective personnel continuing education and training in a modern organisation (a chosen bank X). The theoretical part of this Paper highlights the most important aspects of an effective structure of an organisation’s continuing training system by pointing the need to maintain and develop the personnel’s competences constantly, as well as creating conditions for continuous advancement and perfection of the staff’s professional abilities and skills. The Paper’s practical part focuses on the analysis of continuing education and training in a chosen bank X, and proposals have been worked out to achieve progress of its effectiveness. As a result of the research proposals have been elaborated for the establishment of a training system for new employees, the advancement of a computerised employee training system, as well as the assessment and enhancement of training efficiency. The research can be applied as a modern instructive material for employees of organisations’ training centres who deal with issues related to raising the improvement of the personnel’s performance quality and the raising of human resources value in these organisations.

. Darbs veltīts mūsdienu organizāciju (izvēlētas bankas X) personāla efektīvas tālākizglītības nodrošināšanas problēmu risinājumam. Darba teorētiskā pārskata daļa satur atziņas par organizāciju efektīvas tālākizglītības sistēmas struktūru, akcentējot nepieciešamību nemitīgi uzturēt un attīstīt personāla kompetenci, kā arī radot apstākļus nepārtrauktai darbinieku prasmju un iemaņu pilnveidei un attīstībai. Darba praktiskā pētījuma daļā veikta izvēlētas bankas X tālākizglītības sistēmas analīze un izstrādāti priekšlikumi tās darbības efektivitātes celšanai. Pētījuma rezultātā izstrādāti priekšlikumi arī jauno darbinieku mācību sistēmas izveidei, bankas darbinieku datorizētās mācību sistēmas pilnveidei un mācību efektivitātes celšanai un novērtēšanai. Pētījums var kalpot kā mūsdienīgs izglītojošs materiāls organizāciju personāla mācību centru darbiniekiem, kas risina šo organizāciju personāla darba izpildes kvalitātes un cilvēkresursu vērtības celšanas problēmas.
The system of further education for bank staff.
Keywords: Pedagoģija